The role of farmer groups and agricultural extension services in enhancing rice productivity and farm income - Rudy Nur Hidayah (Institute for Advanced Social, Science, and Sustainable Future, 2026)
Background: The rising national demand for rice has drawn attention as farmers face low rice productivity and inadequate farm income. Farmer groups and agricultural extension agents are predicted to tackle these problems; however, their specific contributions remain unclear. Therefore, this study aims to examine the roles of farmer organizations and extension agents in improving rice productivity and farm income in Indonesia. Methods: This study employed 2024 cross-sectional data covering all provinces of Indonesia, gathered from the Central Bureau of Statistics (BPS) and the Ministry of Agriculture. Further, the data for rice productivity are specific, while the available farm income data represent overall agricultural income due to data limitations. Our study analyzed the data employing two separate multiple linear regression approaches, incorporating composite indices for farmer groups and extension agents, as well as priority province status as control variables to assess the influence of these actors on rice productivity and farm income. Findings: The study finds that neither farmer organizations nor extension agents hava a significant effect on rice productivity. However, farmer organizations display an adverse effect on farm income at the 10% significance level, while extension agents have a positive but statistically insignificant effect. Additionally, the priority province variable shows statistical significance at the 1% level for rice productivity but not for farm income. Conclusion: The findings conclude that strengthening farmer organizations and extension services in Indonesia remains a major concern for improving rice productivity and farm income. Despite these insights, using aggregate farm income data remains a limitation that can not fully reflect the specific economic dimension of rice-based farming. Novelty/Originality of this article: Prior research focused on data from a specific region, whereas this article employs national data to provide a broader analysis of farmer organizations and extension agents.